Functional crosstalk between the mitochondrial PTP and KATP channels determine arrhythmic vulnerability to oxidative stress - Xie, Chaoqin; Kauffman, Justin; Akar, Fadi G. (Frontiers in Physiology, 2014)
Permeability transition pore (mPTP) opening leads to mitochondrial dysfunction & cell death during oxidative stress (OS). However mPTP desensitization with cyclosporine A (CsA) has shown variable efficacy in limiting post-ischemic arrhythmias. We hypothesized that feedback between energy dissipating (mPTP) and cardioprotective (mKATP) channels determine vulnerability to OS. Methods & Results: Guinea pig hearts (N=61) were perfused with H2O2 to elicit mitochondrial membrane potential (MMP) depolarization. Optical mapping was used to measure MMP or action potentials (AP). Hearts were treated with CsA under conditions that altered mKATP activity directly or indirectly via its regulation by PKC. CsA blunted OS-induced MMP depolarization and delayed loss of contractility but did not affect arrhythmia propensity. Surprisingly, prevention of mKATP activation with the phosphatase BDM reversed the protective effect of CsA, paradoxically exacerbating OS-induced MMP depolarization and accelerating arrhythmia onset in CsA treated hearts. To elucidate the putative molecular mechanisms, mPTP inhibition by CsA was tested under conditions of selective PKC inhibition, mKATP activation or blockade. Similar to BDM, CHE did not alter OS-induced MMP depolarization. However, it completely abrogated CsA-mediated protection against OS. Pharmacological block of mKATP, a target of PKC signaling, equally abolished the protective effect of CsA on MMP depolarization, whereas channel activation with DZX protected against MMP depolarization. Conditions that prevented mKATP activation led to accelerated MMP depolarization and early onset of VF in response to OS. Investigation of the electrophysiological substrate revealed accelerated APD shortening in response to OS in arrhythmia-prone hearts. Conclusions: Cardioprotection by CsA requires mKATP activation through a PKC-dependent pathway. Increasing mKATP activity during CsA administration is required for limiting OS-induced electrical dysfunction.